Flipped Classroom As a Millenial Teaching Model - Irnin Agustina Dwi Astuti; Yoga Budi Bhakti; Ria Asep Sumarni; Dwi Sulisworo; Moh. Toifur (Indonesian Review of Physics (IRiP), 2022)
This study is a literature review. The flipped classroom is the latest pedagogical model that has the potential to change the current traditional way of teaching. Flipped classroom emphasizes on learning activities that promote critical thinking and motivation among the students with the assistance of technology. The flipped classroom allows educators to move from ‘the sage on the stage’ to ‘the guide on the side. The basic and simplest form of flipped classroom is students are expected to watch digital resources prior to class. The students are then required to come prepared for class and perform hands-on activities that are related to the digital resources. The digital resources can be in any form such as video, audio or the internet. This allows teachers to spend more time with their students to carry out in class activities and allow immediate response to students’ needs. Student feedback on this pedagogy was generally very positive with many respondents considering it effective and helpful for learning. One of the biggest advantages mentioned by students is that they had the option to watch each video lecture as many times as required to be prepared for class.